Bilateral tubercular ovarian cyst presenting with vertigo - Bose, Chinmoy K (Nepal Journal of Obstetrics and Gynaecology, 2010)
DOI: 10.3126/njog.v4i1.3337 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 60